ANALISIS EFISIENSI PENGGUNAAN FAKTOR FAKTOR PRODUKSI PADA USAHATANI SEMANGKA INUL DI KABUPATEN DEMAK - Dewi Hastuti; Wibowo, Hendri; Malinda, Dewi; Subantoro, Renan (Universitas Medan Area, 2024)
The largest watermelon production in Demak District, Demak Regency is in Bango Village, reaching 7.91/ton and a harvest area of 46/ha with a productivity of 17.2 tons/ha per year based on data from BPS in 2022. The purpose of this study is to determine the factors that affect production, return to scale and efficiency of using Inul watermelon farming production factors. The research was conducted in June 2023, using the survey method. The determination of respondents by purposive sampling was farmers who were active as members of farmer groups and were planting Inul watermelons, as many as 36 farmers. Primary data collection through interviews using questionnaire guidance. Secondary data comes from BPS and literature literature. The production function uses the Cobb-Douglas production function. Data analysis uses multiple linear regression analysis, scale-up analysis of results and production efficiency analysis. Based on the results of the analysis, production factor factors, namely land area, KNO3 fertilizer and pesticides have a real effect on the 95% confidence level while NPK seeds and fertilizers have a real effect on the 90% confidence level. The sum of elasticity in the Cobb Douglas production function is 0.621 < 1, meaning decreasing returns to scale. The ratio between the marginal product value (NPM) of production factors and the price of production factors for land area of 4 means that it is not yet efficient. Meanwhile, seed production factors, NPK fertilizers, KNO3 fertilizers and pesticides with NPMXi / HXi values < 1 mean that the allocation of production factors is inefficient. The use of production factors needs to be increased and the use of seeds, NPK fertilizers and KNO3 fertilizers and pesticides needs to be reduced according to the land area.